2020
DOI: 10.1007/s42399-020-00522-7
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2, an Underestimated Pathogen of the Nervous System

Abstract: Numerous clinical studies have reported neurological symptoms in COVID-19 patients since the spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), apart from the atypical signs of pneumonia. Angiotensin-converting enzyme-2 (ACE-2), a potential receptor for SARS-CoV-2 entry, is expressed on various brain cells and cerebral parts, i.e., subfornical organ, paraventricular nucleus, nucleus of the tractus solitarius, and rostral ventrolateral medulla, as well as in non-cardiovascular areas such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 102 publications
1
52
0
Order By: Relevance
“…Such studies are important, because they can identify which of the NVU cell types may provide the main route of SARS-CoV-2 entry into the CNS. Previous studies indicated that astrocytes, microglial cells, and endothelial cells express ACE2 (30) (74,75). Recently, high expression levels of ACE2 in adult human heart pericytes (76,77) and mouse olfactory bulb pericytes (78) have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies are important, because they can identify which of the NVU cell types may provide the main route of SARS-CoV-2 entry into the CNS. Previous studies indicated that astrocytes, microglial cells, and endothelial cells express ACE2 (30) (74,75). Recently, high expression levels of ACE2 in adult human heart pericytes (76,77) and mouse olfactory bulb pericytes (78) have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 rapidly penetrates into the brain via the olfactory sensory neurons and causes anosmia [ 69 , 70 , 71 ]. A recent postmortem study conducted by brain MRI revealed that COVID-19 olfactory impairment is likely to be restricted to olfactory bulbs [ 72 ] and another study found local inflammation and cytokine release as causative for injury to the olfactory sensory neurons [ 73 ].…”
Section: Covid-19-related Neurological Effectsmentioning
confidence: 99%
“…Severe acute respiratory syndrome coronavirus (CoV) 2 (SARS-CoV-2), a large ssRNA virus, is the causative agent of COVID-19, which primarily attacks the respiratory tract including associated organs. Additionally, the virus has shown to impact various other organs or body systems like the gastrointestinal system, nervous system etc ( Jakhmola et al, 2020a ; Jakhmola et al, 2020b ; Sonkar et al, 2020 ). Currently new variants of SARS-CoV-2 are reported from different regions of the world.…”
Section: Introductionmentioning
confidence: 99%